2012
DOI: 10.1093/annonc/mdr447
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant fatigue in men with hormone-sensitive prostate cancer on long-term androgen deprivation therapy

Abstract: Two-fifths of men with biochemically controlled prostate cancer on long-term ADT report CRF that interferes with function. Management aimed at improving CRF should address depression and pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…There is some prior evidence that clinically relevant fatigue may be more common among ADT recipients with greater concurrent co-morbidities [8]. The present study also identified an association between a higher baseline Gleason score and greater increases in the number of days fatigued raising the possibility that worsening fatigue may be due in part to advanced disease rather than ADT per se.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…There is some prior evidence that clinically relevant fatigue may be more common among ADT recipients with greater concurrent co-morbidities [8]. The present study also identified an association between a higher baseline Gleason score and greater increases in the number of days fatigued raising the possibility that worsening fatigue may be due in part to advanced disease rather than ADT per se.…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with these changes, a significantly higher percentage of ADT−treated patients than controls reported clinically meaningful fatigue at 6 months (33% vs 21%) and 12 months (32% vs. 19%). These figures are less than the 43% rate of clinically meaningful fatigue cases observed in a cross-sectional study of ADT−treated patients conducted by Storey and colleagues [8]. Discrepant findings may be partially explained by differences in methodology.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In contrast, Storey et al [92] found no relationship between age and fatigue, but the age range in the sample was restricted to older adults (mean age=78, range=54-95). None of these studies systematically evaluated the reasons for the association between lower age and higher fatigue.…”
Section: Discussionmentioning
confidence: 85%
“…10 ADT is used to lower male androgens in order to treat prostate cancer and is a mainstay of treatment for both metastatic and localized disease. 86,87 ADT can produce effects, such as depression and fatigue, 88,89 that may indirectly affect cognitive functioning, and may also directly affect cognitive functioning as studies suggest that lower testosterone levels are associated with worse cognitive functioning in healthy older men 90 . In addition, both low testosterone levels and ADT increase the risk of cardiovascular disease, 91,92 which is a known risk factor for dementia.…”
Section: Risk Factors For Crcimentioning
confidence: 99%